The impact of meritocracy on logistics companies during economic crises - Souza, Felipe Liberato; Torres Júnior, Alvair Silveira (Revista de Administração da UFSM, 2021)
Purpose: meritocracy and incentives for innovation are instruments in the search for efficiency and increased productivity. The objective of this work is to demonstrate the correlation between meritocracy and productivity gains that a franchise network presented in a year of economic crisis in Brazil. Design/methodology/approach: the method of qualitative and quantitative approach of this research used experimentation, based on interviews, observation and data analysis. Two groups of companies, which totalized 92 companies and 746 professionals participated of the research. Findings: management based on recognition and reward for employees of a group of companies has shown an increase in productivity of up to 25% in a year of economic recession. In the same period, another group of companies in the same business, but without a meritocracy-based compensation system, achieved a 9% drop. Research limitations/implications: this work suffered from limitations as to the influence of the local economy of each franchise on the results, impacting the comparisons of the groups that participated in the experimental research. Practical implications: logistics companies can use this work to define a meritocratic model that encourages employees to seek innovation in processes and contribute to better operational performance. Social implications: logistics has a strong impact on the competitiveness of companies, from industry to commerce. This work offers visibility of the influence of productivity in logistics companies in the supply chain. Originality/value: this work contributes to the analysis of the influence of meritocracy in people management, especially in times of economic crisis.